PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Silalahi, Adelina Christin; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis study is aimed to examine the influence of corporate social responsibility disclosure, leverage which is proxy by Debt to Equity Ratio and firm size to the financial performance which is proxy by return on assets by the annual financial statements which have been prepared by the manufacturing companies which are listed in Indonesia Stock Exchange. The population has been obtained by using purposive sampling method to the manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2013-2015 periods and based on the predetermined criteria, 41 manufacturing companies have been selected as samples. The analytical method has been done by using multiple linear regressions analysis and the SPSS (Statistical Product and Service Solutions). The result of the research shows that corporate social responsibility disclosure give positive and significant influence to the financial performance. Debt to Equity Ratio (DER) give significant and negative influence to the financial performance. Meanwhile firm size does not give any influence to the financial performance of the company.Keywords: Corporate social responsibility, leverage, firm size, financial performance